Block length effect of decision-aided maximum likelihood phase estimation in coherent optical communication systems - Zhang, S. (2014)
2009 Conference on Lasers and Electro-Optics and 2009 Conference on Quantum Electronics and Laser Science Conference, CLEO/QELS 2009